The use of selected tax tools for the implementation of pro-ecological goals in Poland on the example of cities with poviat rights - Witkowski, Jacek (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: Environmental protection requires action at various levels. Local governments managing the smallest territorially administrative units have been equipped with a number of competences enabling a positive impact on the condition of local natural resources. Their powers include, inter alia, determining the rates of certain taxes along with the possibility of applying preferences that may be aimed at stimulating environment-friendly behavior and the implementation of various pro-ecological goals. Therefore, a research problem can be raised regarding the use of this type of instruments by municipalities to improve the condition of the natural environment. Aim: The purpose of the article is to investigate whether and to what extent local governments managing communes in Poland use their powers in the scope of applying reliefs and exemptions in local taxes to initiate activities involving the protection and proper use of environmental resources. The study covered 63 cities operating with poviat rights, and the analysis covered the resolutions adopted by the city councils of these units in the years 2019–2021. Results: As a result of the research, it was found that the local governments of the largest Polish cities rarely applied exemptions from property tax and transport means tax exemptions due to pro-ecological activities undertaken by taxpayers. Local government officials were much more willing to use the statutory right to apply different tax rates on means of transport depending on the type of drive. In the group of the 10 largest urban centers, only in one case there is no lower tax rate for 2021, and thus no relief for owners of vehicles with a drive that meets certain emission limits or electric power. Importantly, the reliefs were most often accompanied by the reduction or maintenance of the real tax rates at a stable level.